2024
DOI: 10.1038/s41467-023-44664-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual-plasmonic Au@Cu7S4 yolk@shell nanocrystals for photocatalytic hydrogen production across visible to near infrared spectral region

Chun-Wen Tsao,
Sudhakar Narra,
Jui-Cheng Kao
et al.

Abstract: Near infrared energy remains untapped toward the maneuvering of entire solar spectrum harvesting for fulfilling the nuts and bolts of solar hydrogen production. We report the use of Au@Cu7S4 yolk@shell nanocrystals as dual-plasmonic photocatalysts to achieve remarkable hydrogen production under visible and near infrared illumination. Ultrafast spectroscopic data reveal the prevalence of long-lived charge separation states for Au@Cu7S4 under both visible and near infrared excitation. Combined with the advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…That is to say, the red-shift performance of CQDs and their tight combination with TiO 2 can effectively promote the red-shift of the absorption wavelength and effectively inhibit the recombination of electrons and holes. The band gap of CQDs/TiO 2 is reduced relative to that of pure TiO 2 , and the interfacial interaction between CQDs and TiO 2 leads to the redistribution or rearrangement of electron energy levels [ 35 ]. Especially, the biomass origin of CQDs results in a significant number of surface traps for electrons or holes, influencing the band structure of the composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, the red-shift performance of CQDs and their tight combination with TiO 2 can effectively promote the red-shift of the absorption wavelength and effectively inhibit the recombination of electrons and holes. The band gap of CQDs/TiO 2 is reduced relative to that of pure TiO 2 , and the interfacial interaction between CQDs and TiO 2 leads to the redistribution or rearrangement of electron energy levels [ 35 ]. Especially, the biomass origin of CQDs results in a significant number of surface traps for electrons or holes, influencing the band structure of the composites.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the results of FTIR, ultraviolet–visible spectroscopy, and fluorescence spectroscopy showed that there were abundant functional groups on the surface of the CQD/TiO 2 and that the absorption peaks at wavenumbers lower than 1000 cm −1 were the characteristic absorption peaks of Ti-O-C. The band gap of CQD/TiO 2 was reduced compared with that of TiO 2 , and the absorption band shifted to visible light; meanwhile, the interfacial interaction between the CQDs and TiO 2 may lead to the redistribution or rearrangement of electron energy levels [ 35 ]. Furthermore, the XPS results also indicated the variation in the surface elements of the composites, and the results showed that the electron density of the outer layer of Ti increased and the electron-binding energy decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The photothermal performance observed in Au@Cu 7 S 4 , which is expected to exhibit photothermal effects (both Au and Cu 7 S 4 are capable of depositing thermal energy into the lattice vibrations upon LSPR excitation), was very limited, even with a small volume of sample solution and intense laser irradiation. 141 Therefore, it is challenging to sufficiently consider the influence of photothermal effects and to control and optimize the reaction conditions accordingly. We also need to explore other electric effects of carriers that play an important role in photocatalysis and investigate the interactions between electric effects and photocatalysis, which could be of great help in increasing solar energy conversion afterwards.…”
Section: Summary and Overviewmentioning
confidence: 99%
“…Tsao et al's pioneering work on plasmonic Au@Cu 7 S 4 yolk@shell nanostructures represents a significant leap in PC hydrogen production, particularly under near-infrared irradiation. 86 This study stands out as the first to harness the LSPR properties of nonstoichiometric semiconductors for solar hydrogen production, opening a new frontier in the utilization of solar energy. In Figure 10a, the structural and chemical analyses of Au@Cu 7 S 4 revealed the characteristics of yolk@ shell nanostructures.…”
Section: ■ Near-infrared Photoactivitymentioning
confidence: 99%